Fashioning a Novel Biliary Conduit Using Serosal Surface of Stomach and Duodenum in a Case of Complete Destruction of Hepatocholedochus Wall Following Necrotizing Pancreatitis - Bali, Sharadendu; Pattaswamy, Bhavana (Medical Science: Trends and Innovations Vol. 1, 2025)
Choledochoplasty is a surgical option that has been described in the world literature for the management of common bile duct damage. Various procedures have been described for its resolution, with choledochoplasty using gallbladder wall or biliodigestive anastomosis as the most frequently used option. Necrotizing pancreatitis can involve the biliary system due to its close proximity. When the destruction of part or whole of extra-hepatic biliary tree is encountered at operation, the situation may sometimes not be suitable for a biliodigestive anastomosis. The present case report is about such a situation, wherein there was hardly any length of the CHD available at the porta hepatis, and the surgeon had no experience of dissecting out a further length of the CHD from the liver parenchyma. Also, the CHD was not dilated enough for an anastomosis, even if the dissection had been possible. Under such circumstances, the situation was handled by utilizing the serosal surfaces of the duodenum and the pyloro-antral region of stomach to reconstruct a conduit for the flow of bile along natural passage. Post-op recovery was uneventful and the result was heartening.